(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2026)
This study aims to assess and map landslide susceptibility in the Rangamati District of the Chittagong Hill Tracts, a hilly and steeply sloping area undergoing rapid urbanization and extensive deforestation. The region also receives excessive monsoon rainfall, making it highly prone to frequent landslides. Using an integrated geostatistical and geospatial approach, the research incorporates 12 causative factors, including terrain attributes, rainfall variability, geological characteristics, soil properties, proximity to fault lines, proximity to roads and rivers, and land-use changes, to identify high-risk zones. A total of 306 historical landslide events were analyzed, and key environmental factors were processed using geospatial simulation techniques. Kriging interpolation and weighted overlay analysis within a GIS framework were applied to generate susceptibility maps at a 30 m spatial resolution. Model validation was conducted through Union-level community consultations. The results indicate that 57% of the district area is moderately susceptible, 10.41% highly susceptible, and 0.29% very highly susceptible, representing 120 critical pinpoint locations. Baghai Chhari, Barkal, and Langadu were identified as the most vulnerable Upazilas. The key drivers of susceptibility include clay-loam soils, moderate slopes (10–30 degrees), weak sedimentary rock formations, extensive deforestation, heavy monsoon rainfall, and land alteration associated with road construction, 67% of historical landslides occurred within 500 meters of roads, highlighting their influence. The study recommends integrating susceptibility maps into local planning processes, early warning systems, and community-based disaster preparedness initiatives. Addressing landslide susceptibility and reducing associated risks will contribute to achieving SDG 11 (Sustainable Cities and Communities), while safeguarding human lives and biodiversity aligns with SDG 15 (Life on Land). The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(2), 2025, P 193-209